The crises of Palestinian commando action in Lebanon during RASHEED KARAMI cabinet (15 January – 25 November 1969) - AL- Abodey, Dr. Mohammed Jaber Enad (Thi Qar Arts Journal, 2021)
The Palestinian issue has engaged the global opinion in general, but it has engaged the Lebanese public opinion in very special, for it has strong connection among the Lebanese popular middles, and this issue has directly effected on the interior & exterior of Lebanon situations and specifically the commando action in it. It has negative effects on the interior situation in Lebanon and specifically in governmental ministries changing time & time and the military clashes between the army and the resistance .This has made it important and at the same time is related with some Lebanese politicians, so the conversation about it is tainted with bitterness and pain. So the title of the research was Due to the danger of this issue on the Arabian security we would like to talk about it clearly with some details, We have chosen this issue as a subject for our research which is titled "the crises of Palestinian commando action in Lebanon during RASHEED KARAMI cabinet (15 January – 25 November 1969)" when he engaged the cabinet on incident of bombing the airport of Beirut from side and increasing in commando action in the south of Lebanon in the other hand , In time the cabinet of RASHEED KARAMI remained fighting the division in the Lebanese street between supporter & opposition for that action , so some bloody events occurred during that cabinet resulted to be resigned but is had commenced its working for sake to draining its missions in formal status , Ended by Cairo pact in November 1969 , And by this pact the commando action has been started widely in Lebanon but according to conditions between Lebanese government and Palestinian liberation organization.